Pertanggungjawaban Hukum Pejabat Pembina Kepegawaian dan Pejabat yang Berwenang atas Kesalahan dalam Penjatuhan Hukuman Disiplin Pegawai Negeri Sipil - Rony Alfredo Rumapea (SASI, 2019)
Law enforcement is an effort to build legal ideas and concepts that are expected by the people to become a reality. Supervision and the imposition of the right sanctions for indisiplinary and code of ethics violations is needed in the context of law enforcement. The law firmly states that government officers are dishonorably discharged because they are convicted of a criminal offense or criminal offense that has to do with office and / or general crime, including acts of corruption. It is necessary to review the application of appropriate principles and norms to fulfill the accountability of officials who do not use their authority to impose sanctions for violations committed by public servants. We must examine and review various regulations relating using a normative juridical approach to find out how these regulations are implemented in administrative law enforcement. Administrative and criminal legal liability in the form of sanctions must be imposed on the Chief Officer / Authorized Officer.